Silas Bent correspondence - Bent, Silas, 1820-1887.
Letter from Bent to his sister describing his participation in Commodore Matthew C. Perry's expedition to Japan. Includes detailed descriptions of Japan and its people. Accompanied by albumin carte de visite photograph of Bent.
Naval officer and oceanographer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Perry, Matthew Calbraith, -- 1794-1858.; Japan -- Description and travel; Naval officers; Oceanographers